2012
DOI: 10.1097/scs.0b013e3182587a4f
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomy of the Infraorbital Canal and Its Connecting Canals in the Maxilla Using 3-D Reconstruction of Microcomputed Tomographic Images

Abstract: The current study investigated the anatomy of the infraorbital canal (IOC) and its related small canals in the maxilla. Twenty-eight hemimaxillae from human cadavers were studied. The samples were scanned using microcomputed tomography, and then images were three-dimensionally reconstructed using computer software. The branch point of the canal into the anterior superior alveolar nerve from the IOC occurred at about one third along the length of the IOC in the anterior direction. Just over half of the cases ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 2 publications
1
11
0
2
Order By: Relevance
“…They reported multiple ASACs in some cases. They have also stated that ASACs frequently aroused from the 1/5-1/2 anterior portion of IOC with an angle of 37 degree (7). In this study we did not find multiple ASACs.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…They reported multiple ASACs in some cases. They have also stated that ASACs frequently aroused from the 1/5-1/2 anterior portion of IOC with an angle of 37 degree (7). In this study we did not find multiple ASACs.…”
Section: Discussionsupporting
confidence: 53%
“…According to the localization of the IOC, ASAC revealed two different courses as laterally (n = 135, 62.5%) and inferiorly (n =81, 37.5%). Song et al (7). have also reported that lateral course of ASAC according to IOC was more frequent.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The presence of the bony canals of the PSAA with AC may pose a risk during surgical treatments with drilling the alveolar bone on the MS. The IOA and PSAA have supplied to the MS in monkey (Matsukawa, 1969 (Song et al, 2012). Therefore we need to gain information about PSAC for avoid clinical risks using animal model.…”
Section: Introductionmentioning
confidence: 99%